Tinjauan Viktimologis terhadap Kejahatan Penipuan dalam Penerimaan Anggota Polisi Republik Indonesia (Polri) di Polres Rote Ndao - Elvis Hizkia Malelak; Rosalind Angel Fanggi; Sigit Prabowo Sonbait (Pusat Riset dan Inovasi Nasional, 2025)
The purpose of this study is to find out and analyze the extent of the role of victims in the occurrence of fraud crimes in the admission of members of the National Police as well as legal protection efforts for victims of fraud in the admission of members of the National Police in Rote Ndao Regency. This research is an empirical juridical research, so the data used are interviews, literature and literature studies. The data was analyzed descriptively. The results of research in the field show that the victim played a role in the fraudulent act that occurred where the victim gave the perpetrator the opportunity to commit a criminal act by inadvertently having made a bribery attempt to qualify as a member of the Indonesian National Police Force. Legal protection efforts for victims are carried out by following up on reports from victims or repressive efforts, and socializing and educating the public not to easily believe in existing lures or known as preventive efforts and sanctioning the perpetrators by dismissing them so that the same thing does not happen again.